Formability and densification behavior of two-layered structure powder metallurgical hot-pressed Al-Cu/Al composites during hot-upsetting. (April 2021) - Rajasekhar, Kotikala; Babu, V Suresh; Davidson, MJ; Raghavendra, G
An experimental investigation has been performed on the hot formability and densification characteristics of Al-Cu/Al two-layered structure composites. The two-layered composites having different Cu compositions in the Al-Cu layer such as (Cu: 5wt. %, 10wt. %, and 15wt. %) were prepared using the powder metallurgy (P/M) route. The composites were hot-pressed as layer by layer in a steel cylindrical die at 550°C temperature with 0.9 initial relative density (IRD) and 0.1 s −1 strain rate. The preforms were hot deformed between two flat dies with a capacity of 50-ton hydraulic press machine at a temperature range of 150°C – 450°C under triaxial stress state condition. The hot-upsetting behaviour of preforms was analyzed until the cracks begin on the cylindrical preform at the outer surface. The effect of different Cu composition and various deformation temperatures on two-layered preforms were discussed. Results revealed that the (10wt. %Cu) preform achieved good cooperative deformation behaviour between Al-Cu and Al layers at the interface region. The relationship between the process parameters was discussed such as the effect of axial stress (σ z ), relative density ( R ) on axial strain (ε z ) and formability stress index ( β ), different stress ratio parameters (σ θ / σ eff, σ m / σ eff ) on relative density ( R ).